2001
DOI: 10.1081/erc-100107175
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neonatal Hypothyroidism on Leydig Cell Number, Plasma, and Testicular Interstitial Fluid Sex Steroids Concentration

Abstract: We have previously demonstrated that neonatal and transient neonatal hypothyroidism modulates Leydig, Sertoli, and germ cell numbers, sex steroids and androgen binding protein concentration. The present study was undertaken to study the effect of neonatal onset hypothyroidism on Leydig and peritubular myoid cell numbers, plasma and testicular interstitial fluid (TIF) sex steroid concentration at different age groups of Wistar rats. Hypothyroidism was induced by giving 0.05% methimazole (MMI) to lactating mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Recent studies showed that neonatal hypothyroidism decreased the Leydig cell number and increased the mesenchymal=peritubular cells. The opposite trend was observed in T3-induced hyperthyroid rats [68,72,95]. These observations suggest that T3 stimulates the differentiation of mesenchymal cells into Leydig cells.…”
Section: Thyroid Hormones and Leydig Cell Numbermentioning
confidence: 57%
See 2 more Smart Citations
“…Recent studies showed that neonatal hypothyroidism decreased the Leydig cell number and increased the mesenchymal=peritubular cells. The opposite trend was observed in T3-induced hyperthyroid rats [68,72,95]. These observations suggest that T3 stimulates the differentiation of mesenchymal cells into Leydig cells.…”
Section: Thyroid Hormones and Leydig Cell Numbermentioning
confidence: 57%
“…Kalland et al [48] and Cristovao et al [32] found no change in serum testosterone in prepubertal and adult hypothyroid rats, but 376 R. R. M. Maran most reports showed serum T and E2 levels to be low in hypothyroid rats and rams, while an opposite effect was observed in hyperthyroid animals [15, 24-26, 35, 63, 67, 68, 85, 98]. Recently, we reported that low levels of T, DHT, and E2 were found in the plasma and testicular interstitial fluid (TIF) of hypothyroid rats whose hypothyroidism was induced neonatally [68]. Progesterone levels were also decreased in the TIF, while plasma progesterone levels depended on the duration of hypothyroidism [68].…”
Section: Serum Sex Steroids Under Altered Thyroid Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a critical development was the report that thyroid hormone receptors are present in high quantities in neonatal Sertoli cells, indicating that the developing Sertoli cell and testis may be an important thyroid hormone target, even though the adult testis is less dependent (Palmero et al 1988;Jannini et al 1990). For example, hypothyroidism in the neonatal rat impairs testicular growth, germ cell maturation, seminiferous tubule lumen formation, and other developmental events (Palmero et al 1989;Francavilla et al 1991;De Franca et al 1995;Maran et al 2001). Despite the inhibitory effects of hypothyroidism on testicular development, rat pups that are made hypothyroid by the administration of the goitrogen 6-propyl-2-thiouracil (PTU) from birth to day 25 postnatal and then allowed to recover back to a euthyroid state have increases in adult testis size and daily sperm production (DSP) of 80% and 140%, respectively, compared with control animals .…”
Section: Thyroid Hormone Regulates Early Sertoli Cell Developmentmentioning
confidence: 98%
“…This differentiation involves the induction of the cyclin-dependent kinase inhibitor p27 kip1 by the thyroid hormone (T3) (Holsberger et al, 2005a;Holsberger et al, 2003). Hypothyroidism in the neonatal rat impairs testicular growth, germ cell maturation, seminiferous tubule formation and other differentiation processes (De Franca et al, 1995;Maran et al, 2001). Despite the inhibitory effects induced by goitrogen 6-propyl-2-thiouracil (PTU) when administered from birth to postnatal day 25, a dramatic recovery of thyroid hormone levels to the euthyroid state after postnatal day 45 has been observed (Cooke et al, 1991).…”
Section: Introductionmentioning
confidence: 99%